Prevention of Stunting in Children and Pregnant Women Through 4 Healthy 5 Perfect Nutritious Food in Pansor Village - Eliyana, Eliyana; Sapriadi, Sapriadi; Atnika, Atnika; Risnawati, Risnawati; Manasikana, Arina; Kanedi, Ican; Kusairi, Imam; Dendi, Dendi (Jurnal Ilmiah Mandala Education (JIME), 2024)
In Indonesia, one of the health problems that frequently arises is stunting. Currently, Indonesia is ranked 5th in the incidence of stunting in babies in the world. In Indonesia, stunting is called stunting, meaning there are obstacles to physical development and brain development in children. The prevalence of West Nusa Tenggara (NTB) was 24.6%, decreasing to 8.1% compared to information from the Indonesian nutritional status survey (SSGI), where one of the villages, Pansor Village, had 39 standing babies, the aim of carrying out this research activity was To avoid the number of incidents in babies in Pansor village, the approach taken is to provide outreach activities about stunting and its consequences, explaining the dangers of stunting to children to the community, especially mothers with two bodies. Explaining the consumption of nutritious food through demonstration activities for making bonus meals, methods for implementing clean and healthy living behavior through hand washing activities to cadre mothers and mothers of two in the RT. Indeed, 75% of cadre mothers and women with two bodies in Pansor village have undertaken socialization regarding stunting, the result of dedication to the community is that the women of cadres and mothers with two bodies are able to master the movement of washing their hands and making additional food.